The effects of palmar cooling on repeated sprinting ability: a randomized controlled clinical trial - Brown, M.; Daniels, J.; Crabtree, M.; Thompson, K.; Murphy, J.; Pannell, W.; McGlawn, R. (Sensors, 2025)
Highlights: What are the main findings?